ANALISIS DAMPAK EVENT OLAHRAGA SEBAGAI STRATEGI PENGEMBANGAN PEREKONOMIAN DAN PARIWISATA DI KABUPATEN TANJUNG JABUNG TIMUR ( Study Kasus : Sumatera Cup Prix ) - Dwiyono Fitrianto; Reza Hadinata; Wawan Junresti Daya; Endarman Saputra; Ugi Nugraha; Alek Oktadinata (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low level of tourist visits and the suboptimal development of the tourism-based economic sector in East Tanjung Jabung Regency. The presence of the Sumatra Cup Prix (SCP) sporting event at the Zabak National Circuit is seen as a potential sports tourism development strategy that can boost the regional economy and tourist appeal. This study aims to analyze the impact of the SCP on economic and tourism growth, identify post-event infrastructure management strategies, and analyze the development of supporting destinations around the circuit area. The research used a qualitative method with a case study approach. Data collection was conducted through observation, in-depth interviews, documentation, and triangulation of data sources. Research informants included the SCP founder, the Tourism Office, MSMEs, accommodation managers, and the surrounding community. Data analysis used data reduction, data presentation, and conclusion drawing, strengthened by NVivo analysis. The results show that the SCP has a positive impact on increasing MSME income, accommodation occupancy, tourist visits, and strengthening the image of East Tanjung Jabung Regency as a sports tourism destination. However, limited supporting infrastructure and the lack of tourist attractions around the circuit remain obstacles to realizing sustainable economic and tourism benefits for the region.